Risk Factors Associated with Pain on Chronic Intermittent Hemodialysis: A Systematic Review. Issue 2 (5th June 2017) - Brkovic, Tonci; Burilovic, Eliana; Puljak, Livia
Abstract: Objectives: The aim of the study was to define risk factors related to pain in adult end‐stage renal disease (ESRD) patients on chronic intermittent hemodialysis (HD) by developing a systematic review of published data. Methods: The search was conducted from MEDLINE, Scopus, PsycINFO, and the Cumulative Index to Nursing and Allied Health Literature (CINAHL). Manuscripts in all languages were considered. Two authors performed each step independently, and all disagreements were resolved after discussion with the third author. Quality of studies was analyzed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist and Cochrane risk of bias tool. Results: A total of 67 studies with 7, 818 participants were included (median number of participants = 60). Most of the studies reported common factors such as age, gender, body mass index, race/ethnicity, marital status, duration of HD treatment since initiation of HD, different comorbidities, and biochemical parameters. Other studies reported more specific factors such as type, regimen or place of hemodialysis, type of dialyzer, dialysis phase, type of dialyzer membrane, administration site, type of preparation, and dose of erythropoiesis‐stimulating agent (ESA). The studies indicate that these factors may contribute to increased pain in general and also promote development of different pain modalities of various locations and causes in HD patients (eg, pain in general, pain related to arteriovenous access, headache, musculoskeletal pain, ESA application pain). Discussion: Multiple factors for various types of pain in very heterogeneous populations and heterogeneous settings were analyzed in the literature. The results turned out to be inconsistent between the studies. Future large‐scale studies are required, taking into the account limitations of the current evidence base.